The competitiveness of Malaysia logistics industries in preparation for ASEAN service liberalization / Mohd Faizal Sulaiman - Sulaiman, Mohd Faizal (2015)
In today’s world of trade, services sector has become an important engine of the global economy development and this sector continues to grow strongly. As part from the service sectors, logistics activities the backbone to other industries has been seen as a prominent and critical factor in achieving competitive advantage for both industry and country especially in meeting the ASEAN Liberalization. Against these backdrops and in light of the dearth of literature on this area in Malaysia, it is the purpose of this study to assess the competitiveness of Malaysia logistics industry in preparation for the possible challenges on the ASEAN service liberalization, 2015. The project was initiated by Malaysian Logistics Council (MLC) with collaboration with Malaysia Institute of Transport (MITRANS) to carry out logistics and supply chain-related research. Therefore in meeting the objectives of this study, a quantitative method was adopted and the data used in this research was derived from a survey on Malaysia logistics stakeholders. The conciliation of perceptions from Government agencies, logistics providers and users are solicited in gathering insight into the industry’s competitiveness. These were done through several meetings and also distribution of questionnaires to the stakeholders of industry. Evidence from the stakeholders’ shows that the industries are ready for the implementation of liberalization by addressing the effects and benefits will gain from it, however the concerned would be the actual enforcement during the period and several actions need to be taken for further improvements. Nevertheless the key findings on competitiveness exhibit all variables tested have been found strongly related with competitiveness of logistics industry with collaboration give significant impact to the study. This is parallel with current trend where the collaboration and alliances is the most practical to reaching the outer market and at the same time to benefits the synergy between two firms.